Thoracic lymphadenopathy in Asians resident in the United Kingdom: role of mediastinoscopy in initial diagnosis. Issue 2 (February 1985) - Farrow, P R; Jones, D A; Stanley, P J; Bailey, J S; Wales, J M; Cookson, J B
Abstract : Although the incidence of superficial glandular tuberculosis is high in Asian immigrants, a clinical diagnosis without biopsy has previously been shown to be inaccurate in 22% of cases. The role of diagnostic mediastinoscopy and biopsy in thoracic lymphadenopathy was therefore evaluated in 41 consecutive Asian patients. Tuberculosis was diagnosed by histological examination or culture (or both) of gland biopsy material in 24 (59%). A further 12 patients, however, also received antituberculous chemotherapy, with a response in 10 cases. If these are included, 34 (83%) were finally considered to have tuberculosis. The symptoms and ages of the patients with tuberculosis were similar to those typically seen in caucasians with sarcoidosis. Six had tuberculous bilateral hilar lymphadenopathy. In only four cases (10%) was a positive diagnosis other than tuberculosis established; in two (lymphoma and thymoma) mediastinoscopy confirmed preoperative suspicions, and saved only two more (with sarcoidosis and vascular anomaly) from unnecessary antituberculous treatment. Complications included severe haemorrhage (1) and chronic tuberculous sinus in the endoscopy tract (2). Mediastinoscopy is unlikely to change management in most patients, produces an appreciable amount of morbidity, and should be reserved for cases in which there is additional clinical doubt. Any future decline in the prevalence of tuberculosis in Asians may, however, require its further evaluation.